1998
DOI: 10.1161/01.str.29.6.1177
|View full text |Cite
|
Sign up to set email alerts
|

Evidence For Genetic Variance in White Matter Hyperintensity Volume in Normal Elderly Male Twins

Abstract: Background and Purpose-White matter hyperintensities (WMHs), as detected by MRI, are common among the elderly and are frequently interpreted as representing a subclinical form of ischemic brain damage. We used volumetric MR techniques to investigate the contribution of genes and the environment to measures of brain morphology in a sample of community dwelling elderly male twins. Methods-Brain MR (1.5 T) scans were obtained from 74 monozygotic (MZ) and 71 dizygotic (DZ), white, male, World War II veteran twins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
176
1
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 294 publications
(206 citation statements)
references
References 35 publications
(27 reference statements)
27
176
1
2
Order By: Relevance
“…Our approach of studying children within a very narrow age-range allowed an estimation of heritability which is unaffected by age 3 genotype interactions or age-dependent gene expression [Plomin et al, 1997]. Our data are in line with heritability estimates of global brain volumes in adults [BaarĂ© et al, 2001;Carmelli et al, 1998;Geschwind et al. 2002;Pfefferbaum et al, 2000;Posthuma and Boomsma, 2000;Wright et al, 2002] and with a pediatric sample in which a considerable part of the children had already entered adolescence [Wallace et al, 2006].…”
Section: Discussionsupporting
confidence: 77%
“…Our approach of studying children within a very narrow age-range allowed an estimation of heritability which is unaffected by age 3 genotype interactions or age-dependent gene expression [Plomin et al, 1997]. Our data are in line with heritability estimates of global brain volumes in adults [BaarĂ© et al, 2001;Carmelli et al, 1998;Geschwind et al. 2002;Pfefferbaum et al, 2000;Posthuma and Boomsma, 2000;Wright et al, 2002] and with a pediatric sample in which a considerable part of the children had already entered adolescence [Wallace et al, 2006].…”
Section: Discussionsupporting
confidence: 77%
“…Heritability of WMHs was 0.73 in community dwelling elderly male subjects and 0.55 in a large population-based sample of stroke-and dementia-free subjects. 223,224 A high prevalence of WMHs is also found in 22q11-deletion syndrome frequently associated with psychosis, 225 cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy, which is caused by mutations in the NOTCH3 gene on chromosome 19 and frequently associated with depression, and other less common genetic conditions. [226][227][228][229] Nongenetic factors are associated with WMHs as well; [230][231][232][233][234][235][236][237][238] for example, Moore et al 239 reported a correlation between WMH and season of birth in a group of patients with BD.…”
Section: Basal Gangliamentioning
confidence: 99%
“…Prior work using traditional volumetric approaches has shown high heritabilities for major neuroanatomic features [Baare et al, 2001;Bartley et al, 1997;Biondi et al, 1998;Carmelli et al, 1998;Geschwind et al, 2002;Oppenheim et al, 1989;Pennington et al, 2000;Pfefferbaum et al, 2000Pfefferbaum et al, , 2001Posthuma et al, 2000;Scamvougeras et al, 2003;Sullivan et al, 2001;Thompson et al, 2001Thompson et al, , 2004Tramo et al, 1998;White et al, 2002;Wright et al, 2002]. Based on variance component analyses, additive genetic influences appear to account for 52-91% of the total variance in intracranial volume [Carmelli et al, 1998;Pfefferbaum et al, 2000;Posthuma et al, 2000], 62-94% for total brain volume [Bartley et al, 1997;Carmelli et al, 1998;Wright et al, 2002], 82-87% for gray and white matter volumes [Baare et al, 2001], 40-69% for hippocampal volume , and 79-94% for corpus callosum areas [Pfefferbaum et al, 2000;Scamvougeras et al, 2003].…”
Section: Heritability Of Brain Structure In Normal Twinsmentioning
confidence: 99%
“…Based on variance component analyses, additive genetic influences appear to account for 52-91% of the total variance in intracranial volume [Carmelli et al, 1998;Pfefferbaum et al, 2000;Posthuma et al, 2000], 62-94% for total brain volume [Bartley et al, 1997;Carmelli et al, 1998;Wright et al, 2002], 82-87% for gray and white matter volumes [Baare et al, 2001], 40-69% for hippocampal volume , and 79-94% for corpus callosum areas [Pfefferbaum et al, 2000;Scamvougeras et al, 2003]. However, because many aspects of cortical surface geometry differ between individuals, and even between pairs of genetically identical cotwins, quantification techniques that do not account for individual differences in these features may be misleading.…”
Section: Heritability Of Brain Structure In Normal Twinsmentioning
confidence: 99%
See 1 more Smart Citation